Epigenetic programming of T cells impacts immune reconstitution in hematopoietic stem cell transplant recipients - Hardy, Kristine (Blood Adv, 2018)
Immune reconstitution following hematopoietic stem cell transplantation (HSCT) is critical in preventing harmful sequelae in recipients with cytomegalovirus (CMV) infection. To understand the molecular mechanisms underlying immune reconstitution kinetics, we profiled the transcriptome-chromatin accessibility landscape of CMV-specific CD8(+) T cells from HCST recipients with different immune reconstitution efficiencies. CMV-specific T cells from HSCT recipients with stable antiviral immunity expressed higher levels of interferon/defense response and cell cycle genes in an interconnected network involving PI3KCG, STAT5B, NFAT, RBPJ, and lower HDAC6, increasing chromatin accessibility at the enhancer regions of immune and T-cell receptor signaling pathway genes. By contrast, the transcriptional and epigenomic signatures of CMV-specific T cells from HSCT recipients with unstable immune reconstitution showed commonalities with T-cell responses in other nonresolving chronic infections. These signatures included higher levels of EGR and KLF factors that, along with lower JARID2 expression, maintained higher accessibility at promoter and CpG-rich regions of genes associated with apoptosis. Furthermore, epigenetic targeting via inhibition of HDAC6 or JARID2 enhanced the transcription of genes associated with differential responses, suggesting that drugs targeting epigenomic modifiers may have therapeutic potential for enhancing immune reconstitution in HSCT recipients. Taken together, these analyses demonstrate that transcription factors and chromatin modulators create different chromatin accessibility landscapes in T cells of HSCT recipients that not only affect immediate gene expression but also differentially prime cells for responses to additional signals. Epigenetic therapy may be a promising strategy to promote immune reconstitution in HSCT recipients.